Estudo das propriedades magnéticas e estruturais de (Nd, Pr) FeB nanocristalino com adição de TiC e Cr - Franco, Vinicius Cappellano De (My University, 2014)
The addition of both Ti and Cr-C refine the grains in nanocomposites of Nd-Fe-B, increasing substantially the coercive field Hc . This motived our investigation of the effect of the addition of Ti-C and Cr to nanocomposites of Pr-Fe-B and Nd-Fe-B. Ribbons compositions (Pr9,5Fe84,5B6)0,97-x(TiC)0,03Crx (x = 0; 0,0025; 0,005; 0,0075; 0,01) and (Nd9,5Fe84,5B6)0,97-x (TiC)0,03Crx (x = 0,005; 0,01) were produced by melt-spinning. Magnetization measures in fields up to 90 kOe showed that materials containing Cr have substantially higher Hc than the other materials without Cr. For a Pr nanocomposites with 1% Cr, the coercive field Hc was 12.5 kOe, while for a Pr nanocomposites with 0% Cr, Hc = 5.1 kOe. For the sample with 1% Cr, the maximum energy product was approximately 13.6 MGOe, a value limited by the remanence. The X-ray diffractogram analysis showed that the ribbons based on Pr-Fe-B with 1% Cr consist basically of a Pr2Fe14B hard phase and an α-Fe soft phase. Mössbauer spectroscopy was performed at 300 K and showed a reduction of the hyperfine field due to the addition of Cr. Transmission electronic microscopy of the Pr-Fe-B sample with 1% Cr showed that the nanocomposites have a grain size larger than the material without Cr, the microstructure consisting of α Fe grains, with an average size of 100 nm, in a matrix of Pr2Fe14B.
Adições de Ti-C e Cr refinam o grão em nanocompósitos de Nd-Fe-B, aumentando substancialmente o valor de seu campo coercivo Hc. Isto motivou a investigação do efeito da adição de Ti-C e Cr em nanocompósitos de Pr-Fe-B e em outros nanocompóstitos à base de Nd-Fe-B. Fitas metálicas das composições (Pr9,5Fe84,5B6)0,97-x(TiC)0,03Crx (x = 0; 0,0025; 0,005; 0,0075; 0,01) e (Nd9,5Fe84,5B6)0,97-x (TiC)0,03Crx (x = 0,005; 0,01) foram produzidas por resfriamento rápido. Medidas de magnetização em campos magnéticos de até 90 kOe mostraram que os materiais contendo Cr possuem Hc substancialmente maior do que os demais sem. Para um nanocompósito de Pr com 1% Cr, o campo coercivo obtido foi Hc = 12,5 kOe, enquanto que para um nanocompósito de Pr com 0% Cr obtivemos um Hc = 5,1 kOe. O produto energético máximo da amostra com 1% Cr foi de, aproximadamente, 13,6 MGOe, valor este limitado pela remanência. Uma análise do difratograma de raios X mostrou que as fitas à base de Pr-Fe-B com 1%Cr consistem basicamente de uma fase Pr2Fe14B dura e uma fase α-Fe mole. Uma espectroscopia Mössbauer foi realizada em 300 K e mostrou uma redução dos campos hiperfinos devido à adição do Cr. Também foi realizada uma microscopia eletrônica de transmissão na amostra Pr-Fe-B com 1% Cr e os resultados mostraram que o nanocompósito possui um tamanho de grão maior do que o material sem Cr, sendo que a microestrutura majoritária são de grãos constituídos de α-Fe, de tamanho médio de 100 nm, imersos numa matriz de Pr2Fe14B.
Keywords: Engenharia de materiais e metalúrgica; Nanocompósito; (Pr,Nd)-Fe-B; Coercividade; Tamanho de grão; Espectroscopia Mössbauer; Difração de raios X; Microscopia eletrônica de transmissão; Propriedades magnéticas; Adição de Ti-C; Adição de Cr; Materiais magnéticos; Ímas; Nanocomposites; (Pr,Nd)-Fe-B; Grain size; Mössbauer spectroscopy; X-ray diffraction; Transmission electronic microscopy; Magnetic properties; Ti-C addition; Cr addition; Magnetic monopoles; Magnets